2020
DOI: 10.1080/02786826.2020.1839013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the collision rate coefficient between charged iodic acid clusters and iodic acid using the appearance time method

Abstract: Kulmala (2020): Determination of the collision rate coefficient between charged iodic acid clusters and iodic acid using the appearance time method, Aerosol Science and Technology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…The measurement site is located on the west campus of the Beijing University of Chemical Technology, which is close to the west 3rd Ring Road of Beijing. The aerosol size distributions were measured using a homemade particle size distribution system (PSD; Liu et al, 2016) and a homemade diethylene glycol scanning mobility particle spectrometer (Jiang et al, 2011a;DEG-SMPS; equipped with a core-sampling apparatus (Fu et al, 2019). The sulfuric acid monomer and dimer concentrations were measured using a long chemical ionization time-of-flight mass spectrometer (ToF-CIMS; Aerodyne Research, Inc.; Jokinen et al, 2012).…”
Section: Measurementsmentioning
confidence: 99%
“…The measurement site is located on the west campus of the Beijing University of Chemical Technology, which is close to the west 3rd Ring Road of Beijing. The aerosol size distributions were measured using a homemade particle size distribution system (PSD; Liu et al, 2016) and a homemade diethylene glycol scanning mobility particle spectrometer (Jiang et al, 2011a;DEG-SMPS; equipped with a core-sampling apparatus (Fu et al, 2019). The sulfuric acid monomer and dimer concentrations were measured using a long chemical ionization time-of-flight mass spectrometer (ToF-CIMS; Aerodyne Research, Inc.; Jokinen et al, 2012).…”
Section: Measurementsmentioning
confidence: 99%
“…O’Dowd and coworkers ( 3 ) demonstrated that new particles can be produced from condensable iodine-containing vapors. Recent studies ( 4 , 51 ) identified that the cluster formation was sustained by sequential addition of HIO 3 , and although the formation mechanism of HIO 3 is still unclear ( 52 ), the elevated HIO 3 is strongly linked to the photochemistry of IO x . Indeed, the observations of ultrafine particle concentrations in coastal locations are strongly correlated with the rapid processing of IO ( 53 ).…”
Section: Atmospheric Impacts Of Icl and Ibrmentioning
confidence: 99%
“…Note that for different chemical composition of the input particles, the CPC response might be different. Therefore, the kernels used for analysing experiments where particles were formed from oxidised organics (Kirkby et al, 2016) or from iodic acid (He et al, 2021) are different and approximated by the calibration curves for oxidised beta-caryophyllene and sodium chloride from Wlasits et al (2020).…”
Section: Dma-trainmentioning
confidence: 99%
“…We use experiments performed with the differential mobility analyser-train (DMA-train; Stolzenburg et al, 2017) measuring new particle formation and growth at the CERN CLOUD chamber (Duplissy et al, 2016;Kirkby et al, 2011). In addition to testing the method with synthetic DMA-train data (in which the 'correct' results are known), we estimate formation and growth rates from three different formation and growth experiments: sulphuric-ammonia (Stolzenburg et al, 2020), alpha-pinene ozonolysis (Heinritzi et al, 2020) and iodic acid (He et al, 2021;Sipilä et al, 2016). We compare the formation rates with results obtained by using the methodology by Dada et al (2020) based on particle size magnifier (PSM) measurements and the growth rates with the results obtained by the INSIDE method (Pichelstorfer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%